2021
DOI: 10.3389/fnut.2021.652441
|View full text |Cite
|
Sign up to set email alerts
|

Protein Considerations for Athletes With a Spinal Cord Injury

Abstract: Athlete participation in the Paralympic games is steadily increasing; prompting research focused on the unique needs of this population. While the Paralympic Games includes a diversity of athletes, athletes with a spinal cord injury (PARA-SCI) represent a subgroup that requires specialized recommendations. Nutritional guidelines designed to optimize performance, in the context of the neurological impairments, are required. This narrative review summarizes the current literature regarding the importance of diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Therefore, given the lack of recommendations for athletes with disabilities, the use and need for protein after exercise are similar to those of able athletes [ 22 , 23 ]. In contrast, a previous study suggested that compared to able athletes, athletes with disabilities will have lower protein intake because their muscle activity is lower and their overall energy requirements are reduced [ 24 ]. Thomas et al [ 25 ] reported that the recommended daily allowance (RDA) of the able-bodied population is 0.8 g/kg body mass per day, and in able-bodied athletes, the amount of protein required each day ranges from 1.2 to 2.0 g/kg body mass.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, given the lack of recommendations for athletes with disabilities, the use and need for protein after exercise are similar to those of able athletes [ 22 , 23 ]. In contrast, a previous study suggested that compared to able athletes, athletes with disabilities will have lower protein intake because their muscle activity is lower and their overall energy requirements are reduced [ 24 ]. Thomas et al [ 25 ] reported that the recommended daily allowance (RDA) of the able-bodied population is 0.8 g/kg body mass per day, and in able-bodied athletes, the amount of protein required each day ranges from 1.2 to 2.0 g/kg body mass.…”
Section: Discussionmentioning
confidence: 99%
“…Whey protein, as an example, is very well studied and most effective in a dose of 20 to 25 g/dose or 0.3 to 0.4 g/kg/meal to stimulate muscle protein synthesis to a maximal extent consumed following a strength training or an intensive session [45,56]. No study on protein supplementation and its effect on muscle protein synthesis following a training session has been performed in Paralympic athletes [57]. Nevertheless, it seems reasonable to implement a post-session protein intake (20 to 25 g of high-quality protein or 0.3 to 0.4 g/kg/meal) to enhance recovery and adaptation in athletes [58,59].…”
Section: Protein Ingestion To Support Adaptation and Recoverymentioning
confidence: 99%
“…Moreover, planning three to four protein servings over the whole day might further help to improve overall muscle protein synthesis and to minimize muscle protein breakdown [56]. Overall protein intake is recommended to be at least 1.2 g/kg/d [57] in athletes with SCI und and between 1.2 up to 2.2 g/kg/d in athletes with a minimal disability or able-bodied athletes [56]. Protein intake should be increased in case of weight loss and energy restriction.…”
Section: Protein Ingestion To Support Adaptation and Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent publications have highlighted the nutritional aspects that need special attention for para-athletes [ 3 , 6 , 9 , 10 , 11 ]. This has provided some guidance for SCI athletes to address the challenges arising from spinal cord injury on body composition, metabolism, gastrointestinal function, and secondary health issues.…”
Section: Introductionmentioning
confidence: 99%